Monodisperse α-Fe(2)O(3) Mesoporous Microspheres: One-Step NaCl-Assisted Microwave-Solvothermal Preparation, Size Control and Photocatalytic Property - Cao, Shao-Wen (Springer, 2010)
A simple one-step NaCl-assisted microwave-solvothermal method has been developed for the preparation of monodisperse α-Fe(2)O(3) mesoporous microspheres. In this approach, Fe(NO(3))(3) · 9H(2)O is used as the iron source, and polyvinylpyrrolidone (PVP) acts as a surfactant in the presence of NaCl in mixed solvents of H(2)O and ethanol. Under the present experimental conditions, monodisperse α-Fe(2)O(3) mesoporous microspheres can form via oriented attachment of α-Fe(2)O(3) nanocrystals. One of the advantages of this method is that the size of α-Fe(2)O(3) mesoporous microspheres can be adjusted in the range from ca. 170 to ca. 260 nm by changing the experimental parameters. High photocatalytic activities in the degradation of salicylic acid are observed for α-Fe(2)O(3) mesoporous microspheres with different specific surface areas.